Energy Utilization Efficiency and Entrepreneurial Potential of a Solarbiomass Integrated Drying System - Borah, A.; Sethi, L. N.; Sarkar, S.; Hazarika, K. (Journal of Agricultural Engineering, 2018)
In absence of grid power in most of the production catchments in the North Eastern states of India, coupled with disruptive power situation in areas where it is available, agricultural products are invariably dried under traditional sun drying. Ginger and turmeric with high intrinsic qualities are two major spices produced in a formidable quantity in the region. Truckloads of raw ginger are transported to Delhi and other places, causing huge transit losses. A solar-biomass integrated (IDS) batch drying system was thus designed and developed with a capacity of 100 kg/batch. A compound parabolic solar collector coupled with bio-waste fired combustion and heating assembly was designed and attached to a drying chamber consisting of six trays and a wind turbine on the top to create the necessary draft controlled by butterfly valves and sliding gates. Thin layer drying experiments were carried out for drying of sliced ginger and turmeric. Fluidized bed dryer (FBD), electrical oven (EO) and open sun drying (OSD) were used for comparison. Effective moisture diffusivity in case of turmeric drying was nearly 21% more in comparison to ginger drying. Minimum specific energy consumption (SEC) occurred in IDS, and was 14 and 30 times less compared to FBD and OSD, respectively. Considering total heat available in the plenum chamber and latent heat of vapourization, the IDS showed 36.33% of overall energy utilization efficiency. A run up of 10 years and a break-even of 17.70 % was estimated, reflecting high entrepreneurial possibility of the developed IDS.